Prevalence of pediculosis capitis in children from a rural school in Yucatan, Mexico - Manrique-Saide, Pablo; Pavía-Ruz, Norma; Rodríguez-Buenfil, Jorge C.; Herrera Herrera, Roodeth; Gómez-Ruiz, Pilar; Pilger, Daniel (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
We conducted an analytical cross-sectional survey to estimate the prevalence of and factors associated with active head lice infestation. In total 140 children, aged 6 to 16-years, from a public school in rural Yucatan, Mexico, were examined by wet-combing. A structured questionnaire was used to collect information on individuals and the conditions in the surrounding environment. Head lice infestation was found in 19 out of the 140 children tested (13.6%) and this was associated with both lower income (OR 9.9, 95% CI 2.15-45.79, p = 0.003) and a higher frequency of hair washing (OR 8, 95% CI 1.58-50, p = 0.012). Intersectoral control programs that take into account the socioeconomic differences of children should be implemented.